Systematic evolution of bZIP transcription factors in Malvales and functional exploration of AsbZIP14 and AsbZIP41 in Aquilaria sinensis - Zhang, Hao; Ding, Xupo; Wang, Hao; Chen, Huiqin; Dong, Wenhua; Zhu, Jiahong; Wang, Jian; Peng, Shiqing; Dai, Haofu; Mei, Wenli (Frontiers in Plant Science, 2023)
Introduction: Agarwood, the dark-brown resin produced by Aquilaria trees, has been widely used as incense, spice, perfume or traditional medicine and 2-(2-phenethyl) chromones (PECs) are the key markers responsible for agarwood formation. But the biosynthesis and regulatory mechanism of PECs were still not illuminated. The transcription factor of basic leucine zipper (bZIP) presented the pivotal regulatory roles in various secondary metabolites biosynthesis in plants, which might also contribute to regulate PECs biosynthesis. However, molecular evolution and function of bZIP are rarely reported in Malvales plants, especially in Aquilaria trees.Here, 1,150 bZIPs were comprehensively identified from twelve Malvales and model species genomes and the evolutionary process were subsequently analyzed. Duplication types and collinearity indicated that bZIPs is an ancient or conserved TF family and recent whole genome duplication drove its evolution. Interesting is that fewer bZIPs in A. sinensis than that species also experienced two genome duplication events in Malvales. 62 AsbZIPs were divided into 13 subfamilies and gene structures, conservative domains, motifs, cis-elements, and nearby genes of AsbZIPs were further characterized. Seven AsbZIPs in subfamily D were significantly regulated by ethylene and agarwood inducer. As the typical representation of subfamily D, AsbZIP14 and AsbZIP41 were localized in nuclear and potentially regulated PECs biosynthesis by activating or suppressing type III polyketide synthases (PKSs) genes expression via interaction with the AsPKS promoters. Discussion: Our results provide a basis for molecular evolution of bZIP gene family in Malvales and facilitate the understanding the potential functions of AsbZIP in regulating 2-(2-phenethyl) chromone biosynthesis and agarwood formation.